THE ROLE OF MACROBENTHIC COMMUNITIES AS AN INDICATOR FOR THE FERTILITY OF MANGROVE POND: CASE STUDY AT BLANAKAN, SUBANG, WEST JAVA - Joni Haryadi; Hadiyanto Hadiyanto; Mufti Petala Patria (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Macrobenthic in mangrove ecosystems plays an important role as removal particles from the water column to the sediments. Ecology indexes of macrobenthic communities were used in this study as an indicator for the fertility of mangrove pond ecosystems. The study was carried out at mangrove pond in Blanakan, West Java. Data was collected from four sampling sites: opened pond (TB), sylvofishery pond (TS), sedimented pond (TT), and conservation pond (TP). Some ecological indexes such as Margalef’s Index (R), Shannon-Wiener Index (H’), Pielou Evenness Index (E), and Simpson Dominance Index (D) were used to analyze macrobenthic communities. The results showed that infaunal macrobenthic communities were stable at TP with R: 1.91±0.42, H’: 1.59±0.30, E: 0.74±0.14, and D: 0.29±0.12. They were unstable at TB with R: 1.63±0.80, H’: 1.36±0.32, E: 0.74±0.06, and D: 0.35±0.07. The macrobenthic communities can be used as indicator for the fertility of mangrove pond in Blanakan, West Java.